An extended mixture model for the simultaneous treatment of short and long scale interfaces - Márquez Damián, Santiago (2013)
Fil: Márquez Damián, Santiago. Universidad Nacional del Litoral. Facultad de Ingeniería y Ciencias Hídricas; Argentina.